(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The study examined how office technology and management (OTM) skills could predict the attainment of economic productivity of university graduates. Three research questions guided the study. A descriptive research design of survey typed was used. The population comprised 132 postgraduate students of Business Education in Tai Solarin University of Education (TASUED), Ijagun, Ogun State for the academic session 2024/2025. Enumeration technique was used for selecting sample size. Researcher developed questionnaire was used for data collection and it titled ‘Office Technology and Management Skills and Economic Productivity of University Graduates Questionnaire (OTMEPUGQ) with reliability coefficient (r = .96). Descriptive statistics of mean, standard deviation and pie-chart were used for analyzing and presenting research questions 1 and 2. Research question 3 was analyses using Pearson Product Moment Correlation (PPMC). The findings indicated that there was medium level of economic productivity in terms of self-reliance of Business education (OTM) university graduates. It was also revealed that digital, problem-solving, effective time-management, cloud computing, organizational, artificial intelligence and emailing skills were among the required OTM skills for the attainment of university graduates’ economic productivity. The study concluded that there was relationship between office technology and management (OTM) skills and the economic productivity of university graduates (r = 0.682, p <.05). It was recommended that government through university authority should increase and set aside revenue for the management and equipping OTM laboratory with modern technological tools students can play with towards increasing their level of economic productivity.